The application of urban design tools in a complex multi-use site: the case of UJ Sophiatown station and station area as portion of the corridors of freedom - Mtshali, Skhumbuzo (My University, 2018)
As urban populations continue to grow exponentially and cities evolve, mostly in deleterious ways, the demand for good quality urban facilities and infrastructure also increases (Memluk, 2013). In an effort to mitigate the impact of urbanization, and almost equally, the polarization of cities built environment practitioners have been constantly re-thinking their direction of planning and revising their development focus and strategies. Among many others, focus in cities of the global south and almost equivalently cities of the north, has been placed on the improvement public transit systems (increased mobility) and the reconfiguration of the city structure. Much of this has been done through the Bus Rapid Transit – Oriented Development game plan. Proponents of Transit-Oriented Development assert that one of its critical aims is to facilitate increased accessibility and, at least, allow “a degree of human interaction in the public domain – or ‘urbanity’ – that is difficult, if not impossible to achieve in much more socially segregated car dependent urban environments” (Curtis et al, 2009: 3). In the South African context much focus or emphasis has been placed on the former, while neglecting the latter. The research in this reportaims to focus on the South African – Joburg BRT version – the Corridors of Freedom, which was conceived as a BRT-OD since it features more than just buses, bus-ways and stations. To this day, in the context of Johannesburg, a lot of focus has been placed on connecting previously marginalised areas to the city and less focus on connecting the neighbourhoods together (Dittgen, 2017). Dittgen (2017) further states that the corridors should be shaped in a way that makes owning or driving a car becomes a nuisance. The project in this research will focus on the human aspect of the corridor. It will utilise the concept of - THE EVERYDAY - which denotes here and now, ‘the ordinary’, ‘content and context specificity’, ‘actions of people’, ‘reality’, ‘activities of people and domestic rituals’, ‘simple, mundane and ordinary’, ‘lived experience’, ‘repetitive gestures and cycles’, as a point of departure for people-centred urban design (Noero, 2004, Lefebvre and Levich, 1987). Croese (2017) argues that the success of BRT systems in other countries has also been attributed to the idea of creating kilometres of cycling and pedestrian corridors, towards BRT stations, to encourage the use of public transit. According to Cervero (2013) most BRT systems are initiated as mobility investments and less of city-shaping tools. This research aims to understand BRT stations as places of arrival, waiting and departure. It further seeks to analyse the extent to which stations and station areas are connected to their surroundings, particularly adjacent land-uses, and how the impact the users of the site. As emphasised by Jacobs (1993) streets become great as the result of their ability to successfully satisfy both the needs of motorists as conduits and pedestrians as great public spaces to walk.
The everyday :the application of urban design tools in a complex multi-use site: the case of UJ SophiaTown Station and Station area as portion of the corridors of freedom
Thesis is submitted in partial fulfilment for the degree of Master of Urban Design to the Faculty of Engineering and the Built Environment, School of Architecture and Planning at the University of the Witwatersrand, Johannesburg, 2018
Keywords: Urban renewal--South Africa--Johannesburg; City planning--South Africa--Johannesburg; Public spaces--South Africa--Johannesburg